Effects of proximal caries with loss of contact on alveolar bone levels in primary molars of Iraqi children using modified bitewing digital imaging (Mustansiria Dental Journal, 2018)
Destructive forms of periodontal disease can occur in children & adolescents.Proximal caries, gingival inflammation & loss of lamina dura are risk factors indevelopment of alveolar bone loss. This study aims to determine the effect ofproximal caries with loss of contact of primary molars on interdental hard tissuesusing a modified bitewing digital imaging technique .One hundred Iraqi children(7&8 years old) of both sexes were included in this study, half of them havingproximal caries in their primary molars & served as study group & the other halfserved as control. The results showed a significant increase in marginal &interproximal alveolar bone crest height in study group with male predominance. Lossof lamina dura & irregular crestal bone appearance was also evident around primarymolars with proximal caries. Non significant relationship was found between gingivalinflammation & interdental hard tissues. The results indicated that proximal carieswith loss of contact play an important role in development of incipient periodontaldisease in children.